Re-Positioning the Subject: Trainee English Teachers' Constructions of Grammar and English - Upton, Pamela Rose (2005)
There is a requirement, within Key Stages One to Four of the National Curriculum for English, that pupils should be taught various aspects of Knowledge About Language which draw on an explicit understanding of English grammar. Many English teachers find themselves ill-equipped to deal with grammar, not only because they have gaps in their own knowledge, but because they struggle to reconcile the teaching of grammar with the progressive philosophies which have underpinned English teaching in recent decades. A number of studies have explored the philosophies of English teaching. My aim was to examine the perceptions of trainee English teachers on grammar and its place in English teaching within the context of changing definitions of English, and specifically the National Curriculum version that they would be teaching to. A mixture of quantitative and qualitative data from questionnaire surveys and interviews enabled me to make a detailed description of trainees' prior experience of learning grammar and their feelings about teaching it. However, when I came to analyse their understandings of grammar and English, I came up against issues of interpretation and epistemology which caused me to re-think my analytical approach and my overall methodology. The problem was that questions on the meanings of grammar and English teaching had generated a complex, wide-ranging and often contradictory set of responses. I felt a conventional method of coding and analysis could not adequately reflect the intricate, shifting nature of trainee perceptions at this early stage of their apprenticeship. Allied to this were problems of epistemology: the dangers of treating data as fact at a time when the view of my respondents on teaching and on themselves as teachers were in a state of transition. My solution was to change my analytical method, to treat the data as discourse, to use discourse analysis to explore the multiple meanings of English and grammar for trainee teachers and to construct a model which could reflect the fluidity, the contradictions and the potentialities of this discourse. In this way I was able to provide evidence of a transformative process whereby trainee constructions of grammmar were broadening and becoming more compatible with their constructions of English and of themselves as English teachers, while at the same time demonstrating the contradictions and conflicts which continue to characterise subject English.